Calcium Dynamics of Isolated Goldfish (Carassius auratus) Retinal Horizontal Cells: Effects of Oxygen-Glucose Deprivation - Campbell, Benjamin (Université d'Ottawa / University of Ottawa, 2015)
Studies on the survival of central nervous system of hypoxia-tolerant species under challenges of reduced energy availability have characterised adaptive mechanisms of brain at the cell and tissue level that lead to reduced excitability and protection. However, evidence of hypoxic suppression of retinal activity in these species has not been followed up with mechanistic studies. Microspectrofluorometric monitoring of intracellular free Ca2+ concentration ([Ca2+]i) is useful for identifying cellular mechanisms that may lead to adaptive strategies, as unregulated increases in [Ca2+]i cause toxicity. Horizontal cells (HCs) are second order retinal neurons that receive tonic excitatory input from photoreceptors, and possess voltage-gated Ca2+ conductances and other channels that can facilitate toxic increases in [Ca2+]i under conditions of reduced energy availability (modeled as oxygen-glucose deprivation, OGD). It was demonstrated that isolated HCs of the hypoxia-tolerant goldfish display spontaneous, transient [Ca2+]i activity (SA) which decreased in amplitude and area under the curve following OGD or glucose removal (20 min) without recovery. SA was shown to be dependent on extracellular Ca2+ influx through voltage-gated Ca2+ channels, though mechanisms of SA generation and regulation has yet to be determined. Additionally, glutamate-elicited peak increases in [Ca2+]i were reduced after 20 min of OGD. The removal of O2 during OGD insult seemed to be protective as an increase in baseline [Ca2+]i was seen during and following glucose removal under normoxic conditions. The mechanisms mediating these decreases in spontaneous and elicited [Ca2+]i activity are currently unknown, though candidate pathways are discussed. This thesis contributes a hint towards how HCs may tolerate conditions of low energy availability, which may also inform investigations on their role in situ during these insults.
Keywords: Hypoxia; Goldfish; Horizontal Cell; Retina; Ischemia; Oxygen-Glucose Deprivation; Calcium; Microspectrofluorometry